The Validity and Reliability of The Summary of Diabetes Self-Care Activities Questionnaire: An Indonesian Version - Sugiharto Sh; Yu Yun Hsu; Deborah J. Toobert; Shan Tair Wang (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2019)
Introduction: Diabetes self-care activities is a complex regimen, that required an appropriate tools to asses. The Summary of Diabetes Self-Care Activities (SDSCA) questionnaire is the most widely used tool for assess diabetes self-care activities. The study aimed to testing validity and reliability of the Bahasa Indonesia version of the SDSCA. Methods: The study applied a forward-backward translation strategy. A pretest and a validation study were conducted. The Bahasa Indonesia version of the SDSCA was reviewed by an expert panel for conceptual and content equivalence to the English version. Furthermore, forty-five and 125 patients with T2DM participated in the pretest and the validation study, respectively. The psychometric properties were evaluated in terms of internal consistency, content validity, concurrent validity, and construct validity. Results: The content validity index (CVI) and the internal consistency (Cronbach’s alpha) were satisfactory, which are 0.98, and 0.72, respectively. The exploratory factor analysis revealed that SDSCA-I are consistent with the original English version. There are significant correlations between three subscales of SDSCA-I and the diabetes knowledge levels namely general diet (r = 0.274, p = 0.002), physical activity (r = 0.269, p = 0.002), and foot care (r = 0.297, p = 0.001). SDSCA-I was significantly correlated with HbA1c values, in term of general diet (r = -0.205, p = 0.022) and self-monitoring of blood glucose (r = -0.265, p = 0.003). Conclusions: The translation and psychometric test of the SDSCA-I were satisfactory. The tool could assess the self-care activities of Indonesians with T2DM in all settings.